If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying L = 6 * 3 Multiply 6 * 3 L = 18 Solving L = 18 Solving for variable 'L'. Move all terms containing L to the left, all other terms to the right. Simplifying L = 18
| 4(-2x-7)+3x=-53 | | -6x-11=-3x+7 | | ((S+1)(4-s^2))=0 | | 72=18e | | 0.05(7t-4)=0.35(t-3)+0.85 | | 33n+60= | | -9y-6x=0 | | x+x+3x-10=180 | | 33n+6= | | 24r+48= | | m^2-3=29 | | 28u+14= | | 19d=57 | | 10/x=65/40 | | 13x+4y=20000 | | 81z+45= | | 90+2x-6+x=180 | | 32=2(w)+2(4+3w) | | 14*e=2*7 | | m+6+(4m+2)= | | 25a=35 | | 4=y+20 | | 110x+10= | | 42t+7= | | 7/x=2/1.8 | | 2(4v-9)-3(v-11)=-52 | | 2x+6+(6x-1)= | | 2x-y+3z= | | 1-2x=5-6 | | 5/-12 | | -7y=-x+12 | | 1-((x-2)/3) |